Measuring Health Promotion in Sports Club Settings: A Modified Delphi Study. (February 2020) - Johnson, Stacey; Vuillemin, Anne; Geidne, Susanna; Kokko, Sami; Epstein, Jonathan; Van Hoye, Aurélie
Settings-based approaches have become an increasing health promotion focus since the World Health Organization's 1986 Ottawa Charter. While schools, cities, and prisons have implemented this approach, its development within sports environments is recent. Sports are a popular leisure-time activity, requiring validated tools to measure health promotion activity. This study's aim was to develop a measurement tool based on international consensus that measures perceptions of health promotion within sports clubs. It is grounded in the settings-based approach and builds on theory from previous works expanding their context and knowledge. An online, three-round international Delphi study was conducted, inviting experts in sports and health fields to participate in designing the tool. Round 1 created a collaborative list of items; Round 2 validated items based on relevance, importance, and feasibility; and the final round classified items into one determinant category—social, cultural, environmental, or economic. Panelists (69 experts) from 13 countries participated, creating a final list of 62 items at 3 organizational levels; the sports club level included 23 items, the officials level retained 20 items, and the coaching level contained 19 items. This study provides several innovations: (1) applying the settings-based approach to health promotion within sports clubs, (2) defining each club level (sports club, official, coaching) and determinants (social, cultural, environmental, economic) within 3-levels, (3) creating a tool that measures perceptions of health-promotion activities per level and determinant, and (4) obtaining expert consensus on included items. These advancements allow further research on promoting health within sports clubs.